Sea ice projects during NARE 1992/93 - Løyning, Terje Brinck; Vinje, Torgny (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; havis; sjøis

The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting

Proposed terminology and reporting units for sea ice algal assemblages - Horner, Rita A; Syvertsen, Erik E; Thomas, David P; Lange, Carina (Polar Biology, 1988)
Keywords: Antarktis; alger; havis; marin biologi; polarområdene; sjøis

Impact of Grounded Icebergs on the Hydrographic Conditions Near the Filchner Ice Shelf - Nøst, Ole Anders; Østerhus, Svein (Ocean, Ice, and Atmosphere: Interactions at the Antarctic Continental Margin, 1985)
Keywords: Sørishavet; Weddellhavet; havis; hydrografi; isberg; isfjell; isshelf; sjøis; vannmasser

Factors Governing Pelagic Production in Polar Oceans - Sakshaug, Egil; Holm-Hansen, Osmund (Marine Phytoplankton and Productivity: Proceedings of the invited lectures to a symposium organized within the 5th conference of the European Society for Comparative Physiology and Biochemistry — Taormina, Sicily, Italy, September 5–8, 1983, 1984)
Keywords: Sørishavet; fytoplankton; havis; krill; planteplankton; primærproduksjon; sjøis; sjøvann

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Some satellite tracked iceberg drifts in the Antarctic - Vinje, Torgny E (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; oseanografi; sjøis; vannmasser

Conditional instability of sea water at the freezing point - Foldvik, Arne; Kvinge, Thor (Deep Sea Research and Oceanographic Abstracts, 1974)
Keywords: AABW; Sørishavet; bunnvannet; havis; oseanografi; sjøis; sjøvann

The volume of ice in Antarctica - Liestøl, Olav (Norsk Polarinstitutt. Årbok 1961, 1962)
At present c. 15 mill. km• of the earth's surface is covered with ice. Of this area about 85 % falls to the account of Antarctica, 11 % to Greenland and c. 4 % to other areas. From this it is evident that a good knowledge of the ice mass of Antarctica is a deciding factor for the calculation of the total ice volume on earth and its effect on eustatic changes.
Keywords: Dronning Maud Land; glasiologi; havis; havnivåstigning; sjøis

Pelagic whaling in the Antarctic : 4 : The season 1933-1934 - Hjort, Johan; Lie, J; Ruud, Johan T; Hansen, Hans Edvard (I kommisjon hos Dybwad, 1934)
Inneholder også: Limits of the pack-ice in the Antarctic in the area between 40° W and 110° E / by H.E. Hansen. S. 39-41, kart.
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; havis; hvaler; hvalfangst; pelagisk; polarområdene; sjøis